The PDZ3 domain of the cellular scaffolding protein MAGI-1 interacts with the Coxsackievirus and adenovirus receptor (CAR) - Yan, Ran (Int J Biochem Cell Biol, 2015)
The Coxsackievirus and adenovirus receptor (CAR) is an essential cellular protein that is involved in cell-cell adhesion, protein trafficking, and viral infection. The major isoform of CAR is selectively sorted to the basolateral membrane of polarized epithelial cells where it co-localizes with the cellular scaffolding protein membrane-associated guanylate kinase with inverted domain structure-1 (MAGI-1). Previously, we demonstrated CAR interacts with MAGI-1 through a PDZ–domain dependent interaction. Here, we show that the PDZ3 domain of MAGI-1 is exclusively responsible for the high affinity interaction between the seven exon isoform of CAR and MAGI-1 using yeast-two-hybrid analysis and confirming this interaction biochemically and in cellular lysates by in vitro pull down assay and co-immunoprecipitation. The high affinity interaction between the PDZ3 domain and CAR C-terminus was measured by fluorescence resonance energy transfer. Further, we investigated the biological relevance of this high affinity interaction between CAR and the PDZ3 domain of MAGI-1 and found that it does not alter CAR-mediated adenovirus infection. By contrast, interruption of this high affinity interaction altered the localization of MAGI-1 indicating that CAR is able to traffic MAGI-1 to cell junctions. These data deepen the molecular understanding of the interaction between CAR and MAGI-1 and indicate that although CAR plays a role in trafficking PDZ-based scaffolding proteins to cellular junctions, association with a high affinity intracellular binding partner does not significantly alter adenovirus binding and entry via CAR.